Cross‐cultural adaptation and validation of the Karitane Parenting Confidence Scale of maternal confidence assessment for use in Brazil - Lívia W. Pereira; Juliana R. Bernardi; Salete de Matos; Clecio H. da Silva; Marcelo Z. Goldani; Vera L. Bosa (Brazilian Society of Pediatrics, 2018)
Objectives: To transculturally adapt and validate the Karitane Parenting Confidence Scale to the Brazilian Portuguese language and culture and verify the combination of the results with the maternal sociodemographic characteristics. Methodology: This is a validation and transcultural adaptation nestled in a longitudinal and observational study in Porto Alegre, RS, Brazil, assessing mother‐infant pairs from different gestational and perinatal environments. The original authors authorized the translation into Brazilian Portuguese, unified version creation, back‐translation, analysis by specialists, final version implementation, and acceptance. Cronbach's alpha analysis was performed. The Kruskal-Wallis test with post‐hoc Dunn's test was used to compare the study groups. Socioeconomic and demographic characteristics, obtained through a questionnaire in the first 24‐48 h of the newborns' life, were associated with maternal results by the Brazilian version of the scale, using Spearman's correlation and Mann-Whitney's test. Results: The sample consisted of 251 postpartum women, with the confidence maternal questionnaire being applied at 15 days postpartum. The median score of the mothers' confidence was 40.00 (37.00-43.00). The protocol obtained a Cronbach's alpha of 0.717. There were significant weak positive correlations between maternal confidence and age (p = 0.013, r = 0.157) and between maternal confidence and schooling (p = 0.048, r = 0.125). Additionally, a significant association was observed between maternal confidence and parity (p = 0.030). Conclusion: The transcultural adaptation and validation of the confidence maternal questionnaire into Brazilian Portuguese language and culture showed good reliability for this sample. The results of its use demonstrated that maternal confidence was associated with schooling, age and parity.